Dampak Pelatihan Tari Terhadap Rasa Percaya Diri Siswa di MTsN 1 Kota Padang - Hidayatunnisa Hidayatunnisa; Indrayuda Indrayuda (SENDRATASIK UNP, 2023)
This study aims to reveal the impact of dance training on students' self-confidence in MTsN 1 Padang City. This type of research is qualitative research with descriptive methods. The main instrument in this study was the researcher himself and assisted by supporting instruments such as stationery and cameras. the data in this study used primary data and secondary data. Data collection techniques are carried out employing literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and conclusion. The results showed that class VIII students who took part in dance training in extracurricular activities of dance seemed to have a confident attitude. This is reflected through aspects that are represented by several indicators, namely self-confidence, optimism, objectives, and responsibility. The aspect of self-confidence is that students seem to have a fixed stance, will and spirit, this is reflected through every step taken by students who are always confident. The optimistic aspect can be seen from the hopeful and definite idealistic indicators. The objective aspect can be seen from the indicators of impartiality, fairness and openness. The aspect of responsibility can be seen from the indicator of being able to complete tasks and promises. Based on the results of data analysis, the impact of student confidence through the indicators studied, namely self-confidence, optimism, objectives, and responsibility, an increase was influenced by dance training in extracurricular activities at MTsN 1 Padang City.